Can we harness computerised cognitive bias modification to treat anxiety in schizophrenia? A first step highlighting the role of mental imagery. - Steel, C; Wykes, T; Ruddle, A; Smith, G; Shah, D; Holmes, E (2010)
A new wave of computerised therapy is under development which, rather than simulating talking therapies, uses bias modification techniques to target the core psychological process underlying anxiety. Such interventions are aimed at anxiety disorders, and are yet to be adapted for co-morbid anxiety in psychosis. The cognitive bias modification (CBM) paradigm delivers repeated exposure to stimuli in order to train individuals to resolve ambiguous information in a positive, rather than anxiety provoking, manner. The current study is the first to report data from a modified form of CBM which targets co-morbid anxiety within individuals diagnosed with schizophrenia. Our version of CBM involved exposure to one hundred vignettes presented over headphones. Participants were instructed to actively simulate the described scenarios via visual imagery. Twenty-one participants completed both a single session of CBM and a single control condition session in counter-balanced order. Within the whole sample, there was no significant improvement on interpretation bias of CBM or state anxiety, relative to the control condition. However, in line with previous research, those participants who engage in higher levels of visual imagery exhibited larger changes in interpretation bias. We discuss the implications for harnessing computerised CBM therapy developments for co-morbid anxiety in schizophrenia.